Spectrum of spondyloarthritis - Himanshu Pathak; Karl Gaffney (Indian Journal of Rheumatology)
Spondyloarthritis (SpA) comprises a group of related diseases which share similar pathogenesis and clinical manifestations. Although the occurrence of SpA spectrum disorders has been known for some time, it was only in the latter half of the twentieth century that the concept of SpA was formally defined. Advances in radiography and magnetic resonance imaging techniques have led to the development of classification criteria which have aided early diagnosis and effective management. This narrative review summaries the latest developments in our understanding of the concept of SpA.